Larval isolation and brood care in Acromyrmex leaf-cutting ants - Lopes, JFS; Hughes, WOH; Camargo, R. S.; Forti, Luiz Carlos [UNESP] (Birkhauser Verlag Ag, 2005)
The larvae of leaf-cutting ants are maintained within the fungus gardens of their colonies and are fed pieces of fungus by the adult workers. However, little else is known about the nature of the worker-larva interaction in these ecologically important ants. To examine whether workers can gauge the needs of individual larvae, we isolated larvae without adult workers for different lengths of time. We then placed workers with the larvae and recorded the type and frequency of the subsequent behaviours of the workers. Workers scraped the mouthparts of larvae, ingested their faecal fluid, fed them with fungal hyphae, transported them around the fungus garden and, most frequently, licked their bodies. The workers were also observed to 'plant' fungal hyphae on the bodies of larvae. Workers interacted more frequently with larvae that had been isolated without workers than with those that had not, but there was no effect of the length of isolation. The results suggest that the interactions are complex, involving a number of behaviours that probably serve different functions, and that workers are to some extent able to assess the individual needs of larvae.
Keywords: Acromyrmex; larvae; brood; disease; fungal mutualist